2014
DOI: 10.1371/journal.pone.0096512
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid and GM-CSF Coordinately Induce Retinal Dehydrogenase 2 (RALDH2) Expression through Cooperation between the RAR/RXR Complex and Sp1 in Dendritic Cells

Abstract: Retinoic acid (RA)-producing dendritic cells (DCs) play critical roles in gut immunity. Retinal dehydrogenase 2 (RALDH2) encoded by Aldh1a2 is a key enzyme for generating RA in DCs. Granulocyte–macrophage colony-stimulating factor (GM-CSF) potently induces RALDH2 expression in DCs in an RA-dependent manner, and RA alone weakly induces the expression. However, how GM-CSF and RA induce RALDH2 expression remains unclear. Here, we show that GM-CSF-induced activation of the transcription factor Sp1 and RA-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…ALDH1A2 ( aldehyde dehydrogenase 1 family member A2 ), also known as RALDH2 , has been identified to play critical roles in the synthesis of retinoic acid, the active derivative of vitamin A (retinol), which affects mainly body growth and bone development in animals (Ohoka et al . ). FAM84B ( family with sequence similarity 84 member B ) has been suggested as a candidate gene for poor sperm motility in Holstein–Friesian bulls (Hering et al .…”
Section: Significant Snps Identified For Carcass Weight (Cw) In Chinementioning
confidence: 97%
“…ALDH1A2 ( aldehyde dehydrogenase 1 family member A2 ), also known as RALDH2 , has been identified to play critical roles in the synthesis of retinoic acid, the active derivative of vitamin A (retinol), which affects mainly body growth and bone development in animals (Ohoka et al . ). FAM84B ( family with sequence similarity 84 member B ) has been suggested as a candidate gene for poor sperm motility in Holstein–Friesian bulls (Hering et al .…”
Section: Significant Snps Identified For Carcass Weight (Cw) In Chinementioning
confidence: 97%
“…RA is known to enhance RA biosynthesis in murine DCs through a positive-feedback loop [26][27][28]. We previously showed that exposure of human blood monocytes to RA-producing gastric epithelial cells or RA drives RA biosynthesis in the monocytes.…”
Section: Ra Drives Ra Biosynthesis By Human Modcsmentioning
confidence: 99%
“…Figure 1D-F). It is interesting that these are all experimental-based RA-responsive genes with RARE binding sites located in their upstream regionsLoudig et al, 2000;Ohoka, Yokota-Nakatsuma, Maeda, Takeuchi, & Iwata, 2014) or RXR binding sites predicted by PROMO(Farre et al, 2003;Messeguer et al, 2002) (Figure 1D-F). Although the genomic distances between clustered NTD-specific rare variants and RAREs are about 130 bp (ALDH1A2), 1294 bp (CYP26A1), and 1,664 bp (CRABP1) (Figure 1D-F), it is possible that the NTD-specific rare variants could…”
mentioning
confidence: 97%